Legal Steps by Curators as a Form of Legal Protection for Curators Who Carry Out the Task of Settling Bankruptcy Assets - Johannes Joshua Mulia (International Journal of Science and Society, 2020)
This article discusses the perspective of legal protection for the curator, which derives from the phenomenon of curator being sued both criminally and civil while carrying out their duties to settle bankruptcy assets. It is not uncommon for the curator to be litigated with consequences where not only the process of clearing bankruptcy assets is hampered, but the curator also experiences losses because he has to follow the existing legal process. The solutions and forms of legal protection discussed in this article are that the curator as the aggrieved party can also take legal actions against the party deemed to be detrimental as long as it is carried out within the legal framework and code of ethics.